The role of surgical expertise with regard to chronic postoperative inguinal pain (CPIP) after Lichtenstein correction of inguinal hernia: a systematic review - Lange, J. F. M. (Hernia, 2016)
OBJECTIVE: The aim of this study was to evaluate whether a relation exists between surgical expertise and incidence of chronic postoperative inguinal pain (CPIP) after inguinal hernia repair using the Lichtenstein procedure . BACKGROUND: CPIP after inguinal hernia repair remains a major clinical problem despite many efforts to address this problem. Recently, case volume and specialisation have been found correlated to significant improvement of outcomes in other fields of surgery; to date these important factors have not been reviewed extensively enough in the context of inguinal hernia surgery. METHODS: A systematic literature review was performed to identify randomised controlled trials reporting on the incidence of CPIP after the Lichtenstein procedure and including the expertise of the surgeon. Surgical expertise was subdivided into expert and non-expert. RESULTS: In a total of 16 studies 3086 Lichtenstein procedures were included. In the expert group the incidence of CPIP varied between 6.9 and 11.7 % versus an incidence of 18.1 and 39.4 % in the non-expert group. Due to the heterogeneity between groups no statistical significance could be demonstrated. CONCLUSION: The results of this evaluation suggest that an association between surgical expertise and CPIP is highly likely warranting further analysis in a prospectively designed study.